PENGARUH TRANSAKSI DIGITAL PADA PENJUALAN KOPI ABIQU KOTA PALEMBANG - Dwiputri, Ardela; Saputra, Tedy Setiawan; Ramadini, Aidina Syafaroh (E-Prosiding Seminar Nasional Manajemen dan Akuntansi STIE Semarang (SNMAS), 2024)
The purpose of this study is to examine the effect of the application of digital transactions on coffee sales and evaluate the factors that affect the effectiveness of digital transactions. The type of research used is field research (Field Research), which is a study that collects data in the field. This research was conducted at Abiqu Coffee Palembang City. In this study, the authors used qualitative methods. The research data was collected through direct interviews with Abiqu Coffee employees and management using an open-ended questionnaire. The results showed that digital transactions had no effect on the sales of Abiqu Coffee. Although using digital transactions has advantages such as: 1) Ease of Payment, 2) Transaction Security.